2015
DOI: 10.1016/j.str.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenesis of Bacterial Prionoid RepA-WH1 Recapitulates Dimer to Monomer Transitions of RepA in DNA Replication Initiation

Abstract: Most available structures of amyloids correspond to peptide fragments that self-assemble in extended cross β sheets. However, structures in which a whole protein domain acts as building block of an amyloid fiber are scarce, in spite of their relevance to understand amyloidogenesis. Here, we use electron microscopy (EM) and atomic force microscopy (AFM) to analyze the structure of amyloid filaments assembled by RepA-WH1, a winged-helix domain from a DNA replication initiator in bacterial plasmids. RepA-WH1 func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 32 publications
3
49
0
1
Order By: Relevance
“…As in the full length RepA when activated to initiate DNA replication (Giraldo et al, 2003), RepA-WH1 undergoes a conformational change in vitro , coupled to dissociation of protein dimers into monomers, either on transient binding to plasmid-derived DNA sequences (Giraldo, 2007; Gasset-Rosa et al, 2008) or upon templating by RepA-WH1 aggregates themselves (Fernández-Tresguerres et al, 2010). Such process enables the monomers of the highly amyloidogenic mutant A31V of RepA-WH1 to assemble into fibers composed of intertwined tubular helical protein filaments (Giraldo, 2007; Torreira et al, 2015). RepA-WH1 fibers are of amyloid nature, as indicated by Congo red binding (Giraldo, 2007), and by a net increase in the protein β-sheet contents, according to both circular dichroism (Giraldo, 2007; Torreira et al, 2015) and surface-enhanced Raman (Fernández et al, 2016a) spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the full length RepA when activated to initiate DNA replication (Giraldo et al, 2003), RepA-WH1 undergoes a conformational change in vitro , coupled to dissociation of protein dimers into monomers, either on transient binding to plasmid-derived DNA sequences (Giraldo, 2007; Gasset-Rosa et al, 2008) or upon templating by RepA-WH1 aggregates themselves (Fernández-Tresguerres et al, 2010). Such process enables the monomers of the highly amyloidogenic mutant A31V of RepA-WH1 to assemble into fibers composed of intertwined tubular helical protein filaments (Giraldo, 2007; Torreira et al, 2015). RepA-WH1 fibers are of amyloid nature, as indicated by Congo red binding (Giraldo, 2007), and by a net increase in the protein β-sheet contents, according to both circular dichroism (Giraldo, 2007; Torreira et al, 2015) and surface-enhanced Raman (Fernández et al, 2016a) spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…Such process enables the monomers of the highly amyloidogenic mutant A31V of RepA-WH1 to assemble into fibers composed of intertwined tubular helical protein filaments (Giraldo, 2007; Torreira et al, 2015). RepA-WH1 fibers are of amyloid nature, as indicated by Congo red binding (Giraldo, 2007), and by a net increase in the protein β-sheet contents, according to both circular dichroism (Giraldo, 2007; Torreira et al, 2015) and surface-enhanced Raman (Fernández et al, 2016a) spectroscopies. In our efforts to engineer a synthetic bacterial amyloid proteinopathy, we found that the amyloidogenicity of WH1(A31V) in E. coli cells can be boosted displacing its conformational equilibrium toward partial unfolding by fusing a protein to its C-terminus, distinct to the natural WH2 domain in RepA (Giraldo et al, 2003): the monomeric fluorescent protein mCherry (Fernández-Tresguerres et al, 2010; Gasset-Rosa et al, 2014; Molina-García and Giraldo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TheA NTACo-functionalized AuNRs were incubated at 1:10 5 and 1:50 AuNR:H6-RepA-WH1(A31V) molar ratios,w ith protein concentrations of 20 and 0.1 mm, respectively.T his protein forms as table dimer in solution under ab road range of conditions (Scheme 1). [13a, 14,19] However,the observed 5nmred shift of the AuNRs longitudinal localized surface plasmon resonance (LSPR) at both molar ratios,i ndicates the absence of AuNR self-assembly in solution ( Figure 1A,s ee the Supporting Information). [20] This might be expected from the presence of two oppositely anchored H6 groups on the H6-RepA-WH1(A31V) dimers (Scheme 1).…”
mentioning
confidence: 94%
“…[13] This protein undergoes as ubstantial conformational change from soluble stable dimers to metastable aggregation-prone monomers that then assemble into amyloid fibers. [14] RepA-WH1, in particular its hyper-amyloidogenic mutant variant A31V,H 6-RepA-WH1(A31V), causes in bacteria at ype of amyloidosis that shares many features with mammalian neurodegenerative diseases, [15] while remaining bio-safe for humans.…”
mentioning
confidence: 99%
“…The WH1 domain in RepA forms stable dimers in solution. Upon allosteric binding to distinct ligands, dimers dissociate into metastable monomers that subsequently assemble as amyloid oligomers and fibres in vitro (Giraldo, 2007; Torreira et al, 2015). When expressed in E. coli , the hyper-amyloidogenic domain variant RepA-WH1(A31V) forms particles of various sizes, distributed across the bacterial cytosol (Fernández-Tresguerres et al, 2010).…”
Section: Introductionmentioning
confidence: 99%